Antiviral effects of statins. (July 2020) - Gorabi, Armita M.; Kiaie, Nasim; Bianconi, Vanessa; Jamialahmadi, Tannaz; Al-Rasadi, Khalid; Johnston, Thomas P.; Pirro, Matteo; Sahebkar, Amirhossein
Abstract: Introducing statins as possible widely-available drugs for the treatment of viral infections requires an in depth review of their antiviral properties. Despite some inconsistency, a large body of literature data from experimental and clinical studies suggest that statins may have a role in the treatment of viral infections due to their immunomodulatory properties as well as their ability to inhibit viral replication. In the present review, the role that statins may play while interacting with the immune system during viral infections and the possible inhibitory effects of statins on different stages of virus cell cycle ( i.e., from fusion with host cell membranes to extracellular release) and subsequent virus transmission are described. Specifically, cholesterol-dependent and cholesterol-independent mechanisms of the antiviral effects of statins are reported.